Moderating effect of cultural differences on the association between social media use and mental health outcomes in adolescents: A cross-cultural comparison study. - Betul Keles Gordesli; Mary Leamy; Trevor Murrells; Annmarie Grealish (PLoS ONE)
The influence of social media on the mental health of adolescents has been controversial and the findings in the literature are inconclusive. Although prior studies have identified several factors that may cause or trigger the proposed relationship, little is known about the culture-related factors as an underlying mechanism that could explain the complexity of this association. This study addressed this gap by examining the associations between the two domains of social media (i.e., time spent on weekdays and weekends) and two mental health outcomes (anxiety and depression) in adolescents via the moderating effect of horizontal-vertical individualism and collectivism. 299 secondary school students (Mage = 15.21 years; 61% girls) from Türkiye (N = 176), Ireland (N = 70), and England (N = 53) completed self-report surveys. Spending more than four hours on weekdays and weekends was positively associated with anxiety and depression whereas spending more than two hours on social media during weekends was positively associated with anxiety in the entire sample. Horizontal and vertical individualism moderated the association between time spent on social media and depression in the entire sample. The study's strengths and limitations, along with the implications of the findings for future research, are thoroughly discussed.